2021
DOI: 10.1002/ece3.8248
|View full text |Cite
|
Sign up to set email alerts
|

Different responses of soil respiration to environmental factors across forest stages in a Southeast Asian forest

Abstract: Soil respiration (SR) in forests contributes significant carbon dioxide emissions from terrestrial ecosystems and is highly sensitive to environmental changes, including soil temperature, soil moisture, microbial community, surface litter, and vegetation type. Indeed, a small change in SR may have large impacts on the global carbon balance, further influencing feedbacks to climate change. Thus, detailed characterization of SR responses to changes in environmental conditions is needed to accurately estimate car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…It was also found that the aboveground biomass of forbs was negatively related to both soil water recharge and depletion in 20–40 cm layer. These results illustrated the succession theory that changes in soil water increased the survivorship of late‐successional species and, therefore, changed the course of vegetation succession (Rodtassana et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
“…It was also found that the aboveground biomass of forbs was negatively related to both soil water recharge and depletion in 20–40 cm layer. These results illustrated the succession theory that changes in soil water increased the survivorship of late‐successional species and, therefore, changed the course of vegetation succession (Rodtassana et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
“…The soil is gray-brown ultisol which was degraded by shifting agriculture by burning before regeneration ( Chanthorn et al, 2016 ; Chanthorn, Hartig & Brockelman, 2017 ). The bulk density was 1.24 g cm −3 and soil texture was sandy clay-loam with the sand contents of 64.4% and 56.4% as measured in September 2020 and February 2021, respectively ( Rodtassana et al, 2021 ). In 2020, a 20 m tall tower was constructed for installing weather sensors above the forest canopy in the plot.…”
Section: Methodsmentioning
confidence: 99%
“…The YF’s mean canopy height was 15 m, with sparser vegetation coverage compared to the other successional forests. The soil type and soil texture in these forests were classified as gray-brown ultisol and as sandy clay-loam to clay loam, respectively 78 .…”
Section: Methodsmentioning
confidence: 99%